Effects of Boonsimgieum aqua-acupuncture on Serum and Liver Lipid Composition and Antioxidative Capacity in Rats Fed High Oxidized Fat - Jun-Mu Lee; Min-Ki Kim (Korean Pharmacopuncture Institute, 2004)
Effects of Boonsimgieum aqua-acupuncture at Naegweun (HP6) and Taecheung (LV3) on liver and plasma lipid composition and antioxidative capacity were investigated in rat fed high oxidized fat. Concentrations of plasma triglyceride, total cholesterol and LDL-cholesterol showed a tendency to increase in the high oxidized fat diet group. However these values showed a tendency to decrease in aqua-acupuncture groups. HDL-cholesterol showed no significantly different in all the treatment groups. Liver total cholesterol values showed a high in control group, however other treatment groups showed no significantly different. Liver triglyceride concentration showed a high value in control group and Naegweun(HP6) aqua-acupuncture group showed lower value than Taecheung(LV3) aqua-acupuncture group. Plasma GOT and GPT values showed a tendency to increase in high oxidized fat diet group. However aqua -acupuncture groups showed a lower values than control group. The concentration of TBARS in liver and plasma showed a high values in high oxidized fat diet group, however these values showed a tendency to decrease in aqua- acupuncture group. Glutathione peroxidase, superoxide dismutase and catalase activity values showed a low values in high oxidized fat diet group, however these values showed a tendency to increase in aqua-acupuncture groups and in aqua-acupuncture groups, these values showed no significantly different.